2003
DOI: 10.1038/sj.bjp.0705284
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone secretagogues modulate the electrical and contractile properties of rat skeletal muscle through a ghrelin‐specific receptor

Abstract: 1 Growth hormone secretagogues (GHS) exhibit potent growth hormone (GH)-releasing activity through the activation of a pituitary receptor. Here, we consider the possibility that GHS can target a specific receptor in rat skeletal muscle and have a role in the control of muscle function. 2 By means of the intracellular microelectrode technique, we found that in vitro application of hexarelin and L-163,255 dose dependently reduced resting chloride (gCl) and potassium (gK) conductances in rat skeletal muscle. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
31
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 46 publications
0
31
0
1
Order By: Relevance
“…In addition to the smooth muscle, previous studies showed that ghrelin also decrease contractility of cardiac (Bedendi et al, 2003;Soares et al, 2006) and skeletal muscles (Pierno et al, 2003). In the myocardium, PGI 2 release from endocardial endothelial cells was proposed to mediate the inotropic and lusitropic effects of ghrelin (Bedendi et al, 2003;Soares et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the smooth muscle, previous studies showed that ghrelin also decrease contractility of cardiac (Bedendi et al, 2003;Soares et al, 2006) and skeletal muscles (Pierno et al, 2003). In the myocardium, PGI 2 release from endocardial endothelial cells was proposed to mediate the inotropic and lusitropic effects of ghrelin (Bedendi et al, 2003;Soares et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In the skeletal muscle, ghrelin reduces membrane potential, apparently by increasing chloride's permeability. This action is directly dependent of GHSR-1a and is blocked by the specific inhibitor DLys 3 GHRP6 (Pierno et al, 2003). In human vascular smooth muscle, ghrelin appears as the most potent endothelium-independent vasodilator, reversing effectively endothelin-1 (ET-1) mediated constrictions with potency similar to that of adrenomodullin (Wiley and Davenport, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, pathophysiological conditions of skeletal muscle with a reduced value of gCl, such as aging, drug-induced myopathies, and, again, muscular dystrophy, are characterized by elevated [Ca 2ϩ ] i (11,21,22,31,44), while the increase of gCl, occur-ring in slow-twitch muscle during HU, parallels a decrease of both [Ca 2ϩ ] i and PKC signaling (30,56,57). The pathway for activation of the calcium-dependent PKC occurs via a G protein (20); few endogenous ligands can activate the receptormediated PLC/PKC signaling pathways able to modulate gCl, further supporting the key role of the latter for muscle physiology (55,58,72). For instance, ATP-mediated activation of P2Y1 purinergic receptor acutely modulates gCl, likely for adapting muscle performance during exercise and fatigue (23,72).…”
mentioning
confidence: 80%
“…Our previous findings have demonstrated an important modification of skeletal muscle protein function during aging (Desaphy et al 1998;Pierno et al 2003) and that these modifications can be associated with increased ROS levels. During aging, we found a downregulation of the expression of ClC-1, the skeletal muscle chloride channel which is correlated with an abnormal decrease of the resting chloride conductance (g Cl ; Pierno et al 1999Pierno et al , 2009).…”
Section: Introductionmentioning
confidence: 87%